Correlations between pelvic pain, low back pain, and postural stability in healthy young women during the menstrual cycle - Metwally Abd Alhamid, Hosam Magdy; Shehata Kelini, Kerolous Ishak; Ibrahim, Saied Mohamed; Alshimy, Ahmed Magdy (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. The menstrual cycle is governed by hormonal changes and is divided into three phases based on the events in the ovary (ovarian cycle) and uterus (uterine cycle). This study investigated correlations between pelvic pain, low back pain, and postural stability in healthy young women during their menstrual cycle.Methods. Eighty-ﬁve female patients were randomly assigned to participate in this study. The outcome measures were pelvic pain (functional pelvic pain scale [FPPS], low back pain (back pain functional scale [BPFS]), and postural stability (Biodex Bal-ance System).Results. There was a signiﬁcant moderate negative correlation between the FPPS and BPFS scores (r = –0.437, p < 0.001). However, there was no signiﬁcant correlation between FPPS and overall stability index (OSI) scores (r = –0.054, p = 0.625) and BPFS and OSI scores (r = 0.143, p = 0.192).Conclusions. There was a signiﬁcant moderate negative correlation between FPPS and BPFS scores. Many young females experienced pelvic pain related to back pain, which also aﬀected functional ability.
Keywords: pelvic pain; lower back pain; postural stability; menstrual cycle